Synthesis of Mesoporous MWCNT/HKUST-1 Composite for Wastewater Treatment - Rasidi Sule; Ajay K. Mishra (Applied Sciences, 2019)
Metal−organic frameworks (MOFs) (Hong Kong University of Science and Technology (HKUST)-1) have been widely studied using the hydrothermal method. Recently, efforts have also been geared toward the incorporation of multiwalled carbon nanotubes (MWCNTs) into the HKUST-1 MOF to advance its applications for gas storage as well as pollutant removal in wastewater. However, a significant reduction in the MWCNT/HKUST-1 composite surface area has limited its applications. We therefore synthesized HKUST-1 and HKUST-1 impregnated with acid-treated multiwalled carbon nanotubes (FMWCNTs). A large surface area of 1131.2 m2g−1 was obtained after acid treatment of the as-received MWCNTs. HKUST-1 was found to have an average particle diameter of 6.5 to 8 µm with a BET surface area of 1176.66 m2g−1. The FMWCNT/HKUST-1 composites had a BET surface area of 1108.85 m2/g. The addition of FMWCNTs was found to increase the parent MOF pore volume from 0.76 to 1.93 cm3g−1. A BJH desorption cumulative pore size of 6.97 nm was obtained in a composite sample. The maximum adsorption capacity of the composites was found to be greater than 100 mg/g at 298 K. The results obtained indicate that FMWCNT/HKUST-1 nanocomposites are a potential adsorbent for methylene blue (MB) removal in dye synthetic water.